The limits of economic theories and models - Hans Visser (The Central European Review of Economics and Management (CEREM), 2020)
Aim: This article was written out of a felt need to reflect on the relationship between economic theories and models on the one hand and the empirical world as we experience it on the other. The question is in particular whether it is possible for economic models and theories to say anything definitive about the world we live in. ~ Design/Research methods: The article relies on professional publications, both within the field of economics and outside of it. ~ Conclusions/findings: There is much reason for humility, economic models and theories have hardly anything definitive to say about the empirical world, and there is a need for a more varied menu of theories and models and for a listening ear for the needs and fears of the population at large. The best we can do is discussing competing and conflicting views in a polite way. However, this requires a Sprachethik that looks more and more like an endangered species. ~ Originality/value of the article: Recent developments concerning the reach of economic models and theories are related to earlier discussions and a way forward is sketched ~
Keywords: 330; Economic methodology; The role of economists; Teaching of economics; Paradigms / Worldviews